2009
DOI: 10.1073/pnas.0811615106
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity regulates phosphorylation-dependent surface delivery of G protein-activated inwardly rectifying potassium channels

Abstract: G protein-activated inwardly rectifying K ؉ (GIRK) channels regulate neuronal excitability by mediating inhibitory effects of G protein-coupled receptors for neurotransmitters and neuromodulators. Notwithstanding many studies reporting modulation of GIRK channel function, whether neuronal activity regulates GIRK channel trafficking remains an open question. Here we report that NMDA receptor activation in cultured dissociated hippocampal neurons elevates surface expression of the GIRK channel subunits GIRK1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
110
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(123 citation statements)
references
References 36 publications
12
110
1
Order By: Relevance
“…This provides a means to keep individual glutamatergic synapses modifiable (38,39) and to spare them from inhibition through spillover of GABA. A previous study reported that NMDA receptor activation promotes surface expression of Kir3 channels in hippocampal neurons (40), which was paralleled with an increase in basal Kir3 currents and adenosine A 1 -mediated Kir3 currents (41). However, GABA B mediated Kir3 currents were not altered, in apparent conflict with an earlier report (42) and our own findings.…”
Section: Discussioncontrasting
confidence: 84%
“…This provides a means to keep individual glutamatergic synapses modifiable (38,39) and to spare them from inhibition through spillover of GABA. A previous study reported that NMDA receptor activation promotes surface expression of Kir3 channels in hippocampal neurons (40), which was paralleled with an increase in basal Kir3 currents and adenosine A 1 -mediated Kir3 currents (41). However, GABA B mediated Kir3 currents were not altered, in apparent conflict with an earlier report (42) and our own findings.…”
Section: Discussioncontrasting
confidence: 84%
“…dephosphorylation at T320 induced by NMDA receptor signaling, while a PP1/PP2A inhibitor did. This is in agreement with two recent studies showing that (1) GIRK channels are dephosphorylated by PP1 in response to NMDA receptor signaling in a calcineurin-independent manner (Chung et al, 2009), and (2) LTD of NMDA receptor responses, as opposed to LTD of AMPA receptor responses, is dependent on PP1, but not on calcineurin . Our results thus suggest that the phosphatase-cascade model of PP1 activation, or I-1 disinhibition by calcineurin proposed in skeletal muscle cell types and in classical models of LTD in CA1 hippocampal neurons (Lisman, 1989;Mulkey et al, 1993), appear not to be the dominant mode of PP1 activation in cortical neurons.…”
Section: Pp1 Dephosphorylation At T320 Is Mediated Via Auto-dephosphosupporting
confidence: 93%
“…In neurons, an attractive model for hippocampal LTD has been suggested whereby PP1 is activated via dis-inhibition of I-1 after calcineurin-mediated dephosphorylation of pT35-I-1. However, PP1 activation independent of calcineurin has been reported both in CA3-CA1 synapses and hippocampal neurons (Chung et al, 2009). Consistent with this, LTD at CA3-CA1 synapses was found to be normal in I-1 KO mice (Allen et al, 2000).…”
Section: Calcium Influx Via Synaptic Nmda Receptors Activates Pp1supporting
confidence: 59%
See 1 more Smart Citation
“…2C). To further test whether the regulation involves SK2 channel trafficking from recycling endosomes, we examined SK2 channel surface expression in the presence of primaquine, which acutely and selectively inhibits recycling but not endocytosis (20,21). Pretreatment with primaquine dramatically abolished surface expression of SK2 channel, even in the presence of ␣-actinin2 (Fig.…”
Section: Critical Involvement Of Early Endosome-mediated Endocytic Rementioning
confidence: 99%